Desempenho agronômico do algodoeiro naturalmente colorido à adubação nitrogenada no semiárido brasileiro - Tartaglia, Francilene de Lima (Universidade Federal Rural do Semi-Árido, 2018)
Naturally colored cotton has environmental appeal per to the lack of chemical dyeing of the fibers, which generates potentially polluting residues. It is cultivated in the Brazilian semi-arid region with absence of nitrogen fertilization and irrigation, resulting in low fiber yield. The objective of this work was to evaluate the response of naturally colored cotton cultivars when submitted to different doses of nitrogen in the soil, in the semi-arid region of Brazil, in two agricultural crops. The experiment was carried out in a field condition, at the Experimental Farm of Federal Rural University of the Semi-Arid, in the years 2016 and 2017. The experimental design was in randomized blocks, with subdivided plots and four replicates. In the main plots, five nitrogen doses (0, 50, 100, 150 and 200 kg ha-1) were randomized and four cotton cultivars (BRS Safira, BRS Rubi, BRS Topázio and BRS Verde) were split into the subplots. Higher productivity of naturally colored cotton was obtained using the economical doses of 140 kg ha-1 N for the cultivars Rubi and Verde, 150 kg ha-1 N for Topázio and 160 kg ha-1 N for Safira. Greater productivity was achieved with Topázio cultivar and lower with cultivar Verde. An average of R$ 4,320.80 is required to produce one hectare of colored cotton. The items that most cost the production, in order of importance, are labor force and fertilizers. Higher profitability can be obtained with doses of 150; 170; 180 and 190 kg ha-1 of N for Topázio, Rubi, Verde and Safira, respectively. Better economic results were obtained with the cultivar Topázio and smaller with Rubi. Higher gross income and net income are obtained with the commercialization of colored cotton in fiber. Nitrogen accumulated in the colored cotton is directed, in descending order, to seeds (56.3%), leaves (29%), stem (10.6%) and fibers (3.8%). Agronomic efficiency and N recovery efficiency decrease with increasing N rates. The cultivar BRS Topázio is the most responsive to nitrogen fertilization, with higher dry mass production, higher N accumulation, higher efficiency in the use of N and higher harvest index. The cultivar Verde is less responsive to nitrogen fertilization, with lower dry mass production, lower N accumulation and lower agronomic and agrophysiological efficiency in the use of N
Keywords: Gossypium hirsutum L; Dose econômica; Viabilidade econômica; Eficiência no uso de nitrogênio; Acúmulo de nitrogênio; Gossypium hirsutum L; Economical dose; Economic viability; Efficiency in the use of nitrogen; Accumulation of nitrogen; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA